Distinct frequency dependent effects of whole‐body vibration on non‐fractured bone and fracture healing in mice. Issue 8 (14th April 2014) - Wehrle, Esther; Wehner, Tim; Heilmann, Aline; Bindl, Ronny; Claes, Lutz; Jakob, Franz; Amling, Michael; Ignatius, Anita
ABSTRACT Low‐magnitude high‐frequency vibration (LMHFV) provokes anabolic effects in non‐fractured bone; however, in fracture healing, inconsistent results were reported and optimum vibration conditions remain unidentified. Here, we investigated frequency dependent effects of LMHFV on fracture healing. Twelve‐week‐old, female C57BL/6 mice received a femur osteotomy stabilized using an external fixator. The mice received whole‐body vibrations (20 min/day) with 0.3g peak‐to‐peak acceleration and a frequency of either 35 or 45 Hz. After 10 and 21 days, the osteotomized femurs and intact bones (contra‐lateral femurs, lumbar spine) were evaluated using bending‐testing, µ‐computed tomography, and histomorphometry. In non‐fractured trabecular bone, vibration with 35 Hz significantly increased the relative amount of bone (+28%) and the trabecular number (+29%), whereas cortical bone was not influenced. LMHFV with 45 Hz failed to provoke anabolic effects in trabecular or cortical bone. Fracture healing was not significantly influenced by whole‐body vibration with 35 Hz, whereas 45 Hz significantly reduced bone formation (−64%) and flexural rigidity (−34%) of the callus. Although the exact mechanisms remain open, our results suggest that small vibration setting changes could considerably influence LMHFV effects on bone formation in remodeling and repair, and even disrupt fracture healing, implicating caution when treating patients with impaired fracture healing. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1006–1013, 2014.